Pengaruh Teknologi Pengeringan Terhadap Mutu Simplisia Seledri - Sembiring, Bagem Sofianna Br; Fanani, Muhammad Zainal; Jumiono, Aji (Universitas Djuanda, 2022)
The celery plant is one of the vegetable ingredients that is useful as a food flavoring and as a raw material for medicine. Storage of celery in fresh form is not durable’s easily damaged because it contains quotes high water. Drying is one way to preserve celery to make it more durable’s. The activity aims to obtain an effective drying method to produce quality celery Cimplicia. The first step is drying consists of 3 types: oven blower, drying rack (electric), black cloth cover rack, and sunlight (traditional). The next stages of activities include sorting, washing, draining, chopping, drying, and quality analysis. Parameters observed included temperature, humidity, drying time, yield, proximate, flavonoids, and antioxidant activities. The temperature and humidity during the drying process ranged from 41-48⁰C and 36.9-42.5% RH and the drying time ranged from 14-21 hours. The Simplicia water content is below 10%, and the maximum ash content is 12.37%, all according to quality standards. Flavonoid levels and antioxidant activity were significantly different between treatments. The type of drying that is effective in producing quality celery Simplicia is the blower oven (electric). The drying temperature was 41⁰C, the humidity was 36.9%, the moisture content was 8.55%, the ash content was 12.37%, flavonoids were 1.41% and the IC50 value was 697 ppm.